2020
DOI: 10.46328/ijte.82
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Mobile Augmented Reality (MAR) Applications into the 5E Learning Model in Biology Teaching

Abstract: This research aims to determine the effect of MAR′s integration into 5E learning in teaching biology. Particularly, its impact on the academic success of the preservice teachers and their attitudes towards digital technology is studied. To this end, the convergent parallel mixed research method is used. The study was conducted with the 31 preservice science teachers in a General Biology Laboratory Course in the 2018-2019 academic year. As the data collection tools, “Achievement Test with Open-Ended Questions”,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Similarly, a recent study stated that using AR technology may have a potential enhancement of students' learning and attitude toward biology (Weng et al, 2020). Another more recent study concluded that mobile AR applications enhanced students' understanding and learning in Biology, making the course more attractive for them (Kozcu Cakir et al, 2021). The findings of the current study corroborate these earlier works.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similarly, a recent study stated that using AR technology may have a potential enhancement of students' learning and attitude toward biology (Weng et al, 2020). Another more recent study concluded that mobile AR applications enhanced students' understanding and learning in Biology, making the course more attractive for them (Kozcu Cakir et al, 2021). The findings of the current study corroborate these earlier works.…”
Section: Discussionsupporting
confidence: 87%
“…AR can have a recognized positive effect on learning (Kozcu Cakir et al, 2021;Turan & Atila, 2021;Yuen et al, 2011), and the idea of implementing AR within an educational environment appears to be accepted by students and teachers. AR can also be suitable for constructivist orientations (Dunleavy & Dede, 2014), which have been highly stressed for learning in the 21 st century.…”
Section: Augmented Reality In Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Schindler et al (2017), the utilization of computers, web, and cellphones is at its highest level amount to date and expected to persistent increment as innovation turns out to be progressively open, explicitly for clients in developing countries. According to Kozcu Cakir, Guven and Celik (2021), the variety in technological products introduced with the technological development in the world increases the technological utilization by activating individuals' interests and inquisitiveness. Zamfir (2008) mentioned that education today "implies not only a singular, computational use of new technologies, but the promotion of engaged peer interactions with a shared computer activity" (p. 684).…”
Section: Introductionmentioning
confidence: 99%